Cultural aspects of care in obstetrics and gynaecology. Issue 11 (November 2018) - Walker, Kate F.; Gribbin, Claire; Siddiqui, Farah
Abstract: In this article we will explore how cultural differences can impact on health outcomes and how an appreciation of this can improve our interactions with both patients and colleagues and have an impact on obstetrics and gynaecology as a profession.